Peran Siswa Dalam Memecahkan Masalah Ulangan Harian Di Sekolah Dasar - Wa Widiya; Muhammad Yusnan; Wa Canda Rumbati; Evi Febriani; Waode Annurisda; Inang Cahayani (Journal of Humanities, Social Sciences, and Education, 2025)
Daily tests are a form of formative evaluation used to measure students' understanding of learning materials. However, in practice, daily tests often present various problems, such as learning anxiety, lack of student preparedness, and low student motivation and active participation. This literature review aims to examine students' roles in solving problems that arise during daily tests at the elementary school level. The literature review approach was conducted by reviewing various journals and scientific publications from the past five years that discuss students' active role in the learning evaluation process. The study results indicate that students' role in solving daily test problems can be maximized through independent learning strategies, the formation of study groups, self-reflection on test results, emotional and anxiety management, and open communication with teachers. It is also necessary to cultivate students' responsibility for their learning process so that they are not merely objects of evaluation but also active subjects in managing and solving academic problems. The study's conclusions confirm that active student involvement in daily tests significantly contributes to improved learning outcomes and the development of independent learner character. These findings provide important implications for teachers in designing learning and evaluation approaches that empower students.